A cluster randomized trial to assess the impact of clinical pathways for patients with stroke: rationale and design of the Clinical Pathways for Effective and Appropriate Care Study [NCT00673491] - Barbieri Antonella; Marchisio Sara; Panella Massimiliano; Di Stanislao Francesco (BMC, 2008)
Abstract Background Patients with stroke should have access to a continuum of care from organized stroke units in the acute phase, to appropriate rehabilitation and secondary prevention measures. Moreover to improve the outcomes for acute stroke patients from an organizational perspective, the use of multidisciplinary teams and the delivery of continuous stroke education both to the professionals and to the public, and the implementation of evidence-based stroke care are recommended. Clinical pathways are complex interventions that can be used for this purpose. However in stroke care the use of clinical pathways remains questionable because little prospective controlled data has demonstrated their effectiveness. The purpose of this study is to determine whether clinical pathways could improve the quality of the care provided to the patients affected by stroke in hospital and through the continuum of the care. Methods Two-arm, cluster-randomized trial with hospitals and rehabilitation long-term care facilities as randomization units. 14 units will be randomized either to arm 1 (clinical pathway) or to arm 2 (no intervention, usual care). The sample will include 238 in each group, this gives a power of 80%, at 5% significance level. The primary outcome measure is 30-days mortality. The impact of the clinical pathways along the continuum of care will also be analyzed by comparing the length of hospital stay, the hospital re-admissions rates, the institutionalization rates after hospital discharge, the patients' dependency levels, and complication rates. The quality of the care provided to the patients will be assessed by monitoring the use of diagnostic and therapeutic procedures during hospital stay and rehabilitation, and by the use of key quality indicators at discharge. The implementation of organized care will be also evaluated. Conclusion The management of patients affected by stroke involves the expertise of several professionals, which can result in poor coordination or inefficiencies in patient treatment, and clinical pathways can significantly improve the outcomes of these patients. It is proposed that this study will test a new hypothesis and provide evidence of how clinical pathways can work. Trial Registration ClinicalTrials.gov ID [NCT00673491]